Analisis Pemahaman Konsep Oprasi Hitung Perkalian Pada Peserta Didik di Kelas IV SD Negeri Cikerut - Gusty Ekka Fajaryna; Ujang Jamaludin; Reksa Adya Pribadi (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
The purpose of this study was to determine the understanding of the concept of multiplication arithmetic operations on students in class IV SD Negeri Cikerut. This research was conducted on fourth grade students at SD Negeri Cikerut from April to June 2023. The method used in this study was descriptive qualitative. The results of this study indicate that the factors causing the low understanding of multiplication arithmetic operations are students who are lazy to think. To overcome this the teacher provides motivation before entering the material. The teacher gives motivation that mathematics is fun. After giving motivation, the teacher usually gives games that involve math material. Giving motivation aims to foster interest in learning mathematics. So far, the teacher uses the classical method, namely by using hands, concrete objects, reason and colleagues. According to researchers, the use of these methods has not been able to improve the multiplication arithmetic operations of students in class IV. Keywords: Understanding of Concepts, Arithmetic Operations, Multiplication